Papulo necrotic tuberculid :An imitator - Sirka C; Jena S; Padhi T; Mishra S; Mohanty P (Wolters Kluwer Medknow Publications, 2005)
A 22 year old female presented with asymptomatic papules, pustules and crusted lesions appearing in crops over the extensor aspect of both upper and lower limbs, palms and soles and sun exposed part of the back. She also had hypopigmented atrophic scars over the extremities and hyperpigmented macules on palms and soles. She had not responded to topical antibiotic creams and broad spectrum antibiotics in the past. VDRL test was non-reactive and the results of skin biopsy and Mantoux test were suggestive of papulonecrotic tuberculid. She was treated with antitubercular therapy and appearance of new lesions stopped within 4 days.